Prinzen und Prinzessinnen bei den späten Ptolemäern - Gehrke, Hans-Joachim (Gerión. Revista de Historia Antigua, 2006)
This contribution investigates the role and the position of the Ptolemaic princes from the death of Ptolemy V up to the reign of Cleopatra VII, especially in times of war and internal trouble. It concludes tentatively that the monarchic system was more stable during this period than one normally tends to admit. This was particularly due to the people of Alexandria’s loyalty to the kingdom and the dynasty.